1999
DOI: 10.1002/(sici)1097-0045(19991101)41:3<166::aid-pros3>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Ki-67 labeling index to DNA-ploidy, S-phase fraction, and outcome in prostate cancer treated with radiotherapy

Abstract: BACKGROUND Our purpose was to evaluate the relationship of Ki‐67 labeling index (Ki67‐LI) to deoxyribonucleic acid (DNA) ploidy, S phase fraction (SPF), other clinical prognostic factors, and clinical outcome for patients with prostate cancer treated by external beam radiotherapy. METHODS Tissue was retrieved from 42 patients who underwent transurethral resection of the prostate before treatment with external beam radiotherapy between 1987–1993. DNA histogram profiles were classified as diploid (diploid + near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Ki-67 is prognostic for death in patients of watchful waiting cohorts, [198][199][200] prognostic for biochemical relapse in cohorts of patients treated by radical prostatectomy, [201][202][203][204][205][206][207] and is prognostic for disease progression in patients undergoing radiation. [208][209][210][211][212] In most of these studies, Ki-67 has an independent prognostic value, which implies that it does add prognostic information upon Gleason score and serum PSA levels. In spite of this apparently overwhelming evidence from multiple independent studies, which probably make it the most oftenconfirmed prognostic biomarker, Ki-67 has still not entered clinical practice.…”
Section: Protein Markers --Immunohistochemistrymentioning
confidence: 99%
“…Ki-67 is prognostic for death in patients of watchful waiting cohorts, [198][199][200] prognostic for biochemical relapse in cohorts of patients treated by radical prostatectomy, [201][202][203][204][205][206][207] and is prognostic for disease progression in patients undergoing radiation. [208][209][210][211][212] In most of these studies, Ki-67 has an independent prognostic value, which implies that it does add prognostic information upon Gleason score and serum PSA levels. In spite of this apparently overwhelming evidence from multiple independent studies, which probably make it the most oftenconfirmed prognostic biomarker, Ki-67 has still not entered clinical practice.…”
Section: Protein Markers --Immunohistochemistrymentioning
confidence: 99%
“…An even more limited number of studies have produced mixed results after examining DNA ploidy as a biomarker for prostate cancer patients treated with radiation therapy [80-85]. …”
Section: Tissue Biomarkers For Prostate Cancer Radiation Therapymentioning
confidence: 99%
“…The Ki-67 antigen is a biomarker used to determine proliferative rate for many other types of tumors [120], as well as been shown to correlate with clinical outcomes of prostate cancer patients treated with surgery or radiation therapy [80, 108, 109, 121-128]. One previous study had suggested a Ki-67 index of ≥3.5% was prognostic for PSA failure following radiation therapy [126].…”
Section: Tissue Biomarkers For Prostate Cancer Radiation Therapymentioning
confidence: 99%
“…La expresión media de células con Ki67 era de 7,5% y tenía un alto poder predictivo para la supervivencia. Khoo VS et al en 1999 46 contrastaron la relación entre Ki67 y ploidía con la evolución del cáncer de próstata después de tratamiento con radioterapia externa. En los resultados distinguieron 3 categorías de tumores: Tumores con positividad de Ki67 ≤al 1,5%; tumores con positividad de Ki67 entre 1,5 y 3,5%; tumores con positividad de Ki67 en un porcentaje mayor del 3,5%.…”
Section: Ki67 Para Evaluar La Respuesta Al Tratamientounclassified